HUBUNGAN MEDIA INFORMASI DAN PERSEPSI WANITA USIA SUBUR TERHADAP PEMERIKSAAN IVA DI WILAYAH KERJA PUSKESMAS KUOK TAHUN 2017 - Miftahur Rahmi (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Cervical cancer is the second most common cancer after breast cancer is most often foundin Indonesian women and can be prevented by detecting the IVA examination. The purposeof research to analyze the relationship of information media and perception of women ofchildbearing age to IVA examination in work area of Public Health Center of Kuok Year2017. This research type use analytical research design with cross sectional design.Sampling technique using systematic random sampling with the population of 914 peopleand the number of samples 90 women of childbearing age. The instrument used is aquestionnaire. Of the 90 respondents, there are 6 (6.7%) of people who perform IVAexamination. Result of bivariate analysis based on chi square test there is a verymeaningful relationship between information media with IVA examination with p value =0,036 (<0,05) (OR = 7,882) and there is very significant relation between perception withexamination of IVA with p value = 0,013 (<0.05) (OR = 14,091). It is hoped that healthworkers themselves will conduct early detection program of cervical cancer so that thepatient can be detected before it becomes acute and for the next researcher can continuethis research with different variables.Keywords: Information Media, Perception, IVA Examination